Vibration response of FG-CNT-reinforced plates covered by magnetic layer utilizing numerical solution - Cao, Yan (Techno-Press, 2020)
Vibration response in a sandwich plate with a nanocompiste core covered by magnetic layer is presented. The core is armed by functionalyy graded-carbon nanotubes (FG-CNTs) where the Mori-Tanaka law is utilized assuming agglomeration effects. The structure plate is located on elastic medium simulated by Pasternak model. The governing equations are derived based on Mindlin theory and Hamilton’s principle. Utilizing diffrential quadrature method (DQM), the frequency of the structure is calculated and the effects of magnetic layer, volume percent and agglomeration of CNTs, elastic medium and geometrical parameters of structure are shown on the frequency of system. Results indicate that with considering magnetic layer, the frequency of structure is increased.